Rendering Houses in Ladakh - Day, Sophie (Home, 2023)
Sophie Day explores the houses that are imagined, built, repurposed, and dismantled among different communities in Ladakh, drawing attention to the ways in which houses are like and unlike people.A handful of in-depth 'house portraits' are selected for the insight they provide into major regional developments, based on the author's extended engagement since 1981. Most of these houses are Buddhist and associated with the town of Leh. Drawing on both image and text, collaborative methods for assembling material show the intricate relationships between people and places over the life course. Innovative methods for recording and archiving such as 'storyboards' are developed to frame different views of the house. This approach raises analytical questions about the composition of life within and beyond storyboards, offering new ways to understand a region that intrigues specialists and non-specialists alike.